Cost of Providing Consumer Credit: A Study of Four Major Types of Financial Institutions - Smith, Paul (Journal of Finance, 1962)
The object of the National Bureau of Economic Research is to ascertain and to present to the public important economic facts and their interpretation in a scientific and impartial manner.The Board of Directors is charged with the responsibility of ensuring that the work of the National Bureau is carried on in strict conformity with this object.2.